2006
DOI: 10.1111/j.1447-0756.2006.00435.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo expression and antitumor activity of p53 gene transfer with naked plasmid DNA in an ovarian cancer xenograft model in nude mice

Abstract: In this report we demonstrated that: (i) naked DNA represents an efficient gene transfer in the SKOV3 xenograft model; (ii) restoration of wt-p53 gene allows tumor growth inhibition; and (iii) this inhibition could be correlated with p53 expression as seen in 84% of treated mice after repeated naked DNA injections. These results allow us to envisage naked DNA as a therapeutic adjuvant in ovarian cancer treatment, concomitantly with tumor resection and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Mutations in the p53 tumor suppressor gene are found in ~50% of advanced stage carcinomas and the apoptotic inhibitor, Bcl-2, is overexpressed in ~40-60% of epithelial ovarian carcinomas (13,14). Restoration of p53, PTEN and ARH1 expression reduces the malignant phenotype of tumor cells (15)(16)(17). PDCD5 is a strong candidate of apoptosis-regulated protein.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the p53 tumor suppressor gene are found in ~50% of advanced stage carcinomas and the apoptotic inhibitor, Bcl-2, is overexpressed in ~40-60% of epithelial ovarian carcinomas (13,14). Restoration of p53, PTEN and ARH1 expression reduces the malignant phenotype of tumor cells (15)(16)(17). PDCD5 is a strong candidate of apoptosis-regulated protein.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have indicated that direct injection of naked DNA failed to show any antitumor activity (Dowty et al 1995). In this manner, although some studies have shown antitumor activity with naked pCMV/p53 plasmids (Collinet et al 2006), they required electroporation or radiation, to be able to achieve significant effects. As shown in Figure 1, the suppression of tumor growth was strictly dependent on the SiNp1 formulation because injection of pCMV/p53 without nanoparticles had no effect on tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Despite low transfection efficiencies of 1% and <0.1% for H-322 and H-358, respectively, repeated injections of naked DNA encoding Bax or p53 inhibited the growth of 4-mm reestablished H-322 tumor (2 out of 4 mice remained tumor free until day 84) or growth retardation for H-358 in a fraction of the animals was reported. Recently, tumor inhibition has been correlated with p53 expression in 84% of treated mice after repeated naked DNA injections in an OC xenograft model in nude mice [19]. These results allow us to envision naked DNA as a therapeutic adjuvant in OC treatment, particularly in concomitance with tumor resection and chemotherapy.…”
Section: Naked Dnamentioning
confidence: 95%
“…Treatments with a combination of cisplatin and adenovirus-p53 have been shown to enhance apoptosis and ovarian tumor regression both in vitro and in animal models [19]. Many Ad vectors with cancer specific conditional replication properties have been preclinically evaluated.…”
Section: Tumor Suppressor Gene Therapymentioning
confidence: 99%